Bile acids in patients with uncontrolled Type 2 Diabetes Mellitus: the effect of two days of oatmeal treatment - Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; Scharnagl, Hubert; Fauler, Günther; Stojakovic, Tatjana; März, Winfried; Kleber, Marcus E.; Lammert, Alexander (Experimental and clinical endocrinology & diabetes, 2020)
Background Beta-glucans are effective in binding bile acids (BA) thereby lowering cholesterol concentration. This might contribute to the beneficial effects of the consumption of β-glucan-rich foods like oatmeal on glucose homeostasis. Objective We measured BA serum concentrations in patients with uncontrolled type 2 diabetes (T2DM) to investigate the effect of two days of oatmeal treatment on BA concentration as compared to a conventional T2DM-adapted diet. Methods The OatMeal And Insulin Resistance study was performed as a randomized, open label crossover dietary intervention study with consecutive inclusion of 15 patients in an inpatient clinical setting. Bile acids were measured by high-resolution mass spectrometry. For statistical analysis, the differences in the concentration of serum BA and laboratory parameters between the fifth day and the third day of each inpatient stay were calculated and the effect compared between both phases by using the Wilcoxon test. Results Whereas there was a mean decrease in total BA following oatmeal treatment (−0.82±1.14 µmol/l), there was no decrease following the control treatment. Glycocholic acid was lower after oatmeal treatment but higher following control treatment (−0.09±0.17 vs. 0.05±0.11 µmol/l). The reduction in total BA was directly correlated with a decrease in proinsulin during the oatmeal phase. Decreases in blood lipids or apolipoproteins were mostly greater after oatmeal treatment, but these differences were not statistically significant. Conclusion Two days of oatmeal diet led to significant reductions in total BA as compared to a diabetes-adapted control diet. The magnitude of BA reduction was directly correlated with a decrease in proinsulin.
Artikel online veröffentlicht: 2. Januar 2020
Gesehen am 09.01.2026